Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0139274
|View full text |Cite
|
Sign up to set email alerts
|

Functional Domains of ZFP809 Essential for Nuclear Localization and Gene Silencing

Abstract: Zinc finger protein 809 (ZFP809) is a member of the Kruppel-associated box-containing zinc finger protein (KRAB-ZFP) family, and is highly expressed in mouse immature cells. ZFP809 is known to inhibit the expression of transduced genes driven by Moloney murine leukemia virus (MoMLV)-typed retroviral vectors by binding to the primer binding site (PBS) located downstream of the MLV-long terminal repeat (LTR) of the vectors and recruiting protein complexes that introduce epigenetic silencing marks such as histone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been shown to inhibit the transcriptional expression of MoMLV and is required for the silencing of endogenous retroviruses (ERVs) during mouse embryonic development [1,11]. Furthermore, domains with diverse functions have been shown within ZFP809 [12,13]. Here we discuss the functions and features of functional domains within ZFP809 in light of the findings of recent studies.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…It has been shown to inhibit the transcriptional expression of MoMLV and is required for the silencing of endogenous retroviruses (ERVs) during mouse embryonic development [1,11]. Furthermore, domains with diverse functions have been shown within ZFP809 [12,13]. Here we discuss the functions and features of functional domains within ZFP809 in light of the findings of recent studies.…”
Section: Introductionmentioning
confidence: 87%
“…binding to the PBS. We investigated subcellular localization, gene silencing ability, and binding ability to the MLV-PBS using a series of truncated and mutated ZFP809 proteins [12,13]. We revealed that the KRAB domain is required for nuclear localization and silencing of transgene expression driven by the MLV-LTR and bind to the MLV-PBS in conjunction with the zinc fingers (Figure 1B) [12,13].…”
Section: Biochemistry and Molecular Biology Journal Issn 2471-8084mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a novel function of the KRAB domain has been recently highlighted. Indeed, published data showed that the zinc finger domains, while possessing NLSs [ 39 , 40 , 41 ], cooperate with the KRAB domain for the nuclear localization of KRAB-ZFPs [ 42 , 43 , 44 ]. In detail, in their elegant papers, Wang and colleagues used mutagenesis studies and confocal microscopy analysis to show that the KRAB domain and zinc fingers collaborate for nuclear localization, but they also display different subnuclear targeting activities.…”
Section: The Human Znf224: the Multifunctional Prototype Among The Krab-zfpsmentioning
confidence: 99%